Waqf and Technology on Academic Publication - Riani, Ririn (Islamic Social Finance, 2024)
This study aims to see the development of research on the topic of "Waqf and Technology" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Waqf and Technology" which comes from the Dimension database with a total of 291 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Waqf and Technology" research development in the world. The results of the study found that there were 4 clusters with the most used words being waqf, development, institution, zakat, country, challenge, intention, and blockchain. Then, the research path topics related to Waqf and Technology are Crowdfunding Waqf, Digital Technology for Distribution of Waqf, Fintech Applications for Waqf Endowment, and Technology Adoption in Waqf Management.